THE AESTHETIC AND DISCURSIVE PRESENCE OF TELEVISION ON PEDRO ALMODÓVAR’S CINEMA - Dra. Andoni ITURBE TOLOSA (Fonseca, Journal of Communication, 2023)
This article is focused on the regular and constant presence of TV in Pedro Almodóvar’s movies. Television, starting from Almodóvar´s first film (Pepi, Luci, Bon y otras chicas del montón, 1980), acquires relevance that will be the object of study from a discursive and aesthetic point of view. The methodology consists in the bibliographic research and the analysis of the scripts, drafts, press kits and films.